From Compliance to Internalization: Buddhist Chanting and Character Formation through Kelman's Theory and the Abhidhamma - Edi Priyono; Euis Dewi Yuliana; I Putu Sarjana; Hendri Hermawan; Dian Tika Sujata; Dariyanti (Center for Research and Publication (PUSLITPEN), UIN Syarif Hidayatullah Jakarta, 2026)
Character education increasingly draws on religious and contemplative practices, yet how repeated ritual practice becomes internalized as character remains underexplored. This study examines character formation through chanting practice among students at the Institut Nalanda Jakarta dormitory by integrating Kelman’s theory of attitude change with the Abhidhamma perspective. Using a qualitative phenomenological design, data were gathered through in-depth interviews with six purposively selected students, participant observation, and documentation, and analyzed interpretively. The findings show that chanting fosters character development through three processes: compliance, identification, and internalization. Students first participate because of institutional norms, then build social bonds through shared participation, and finally internalize the values as personally meaningful. From the Abhidhamma perspective, this transformation is interpreted through citta and cetasika, which underpin mindfulness, self-control, and ethical conduct. The study proposes an Attitude Change Pyramid modelling the movement from external practice to internalized character, offering a transferable lens for religiously grounded character education.